(untitled) (Journal of Global Humanities and Social Sciences, 2024)
With the rapid development of the civil engineering industry, the "Engineering Mechanics" course in civil engineering majors, as a basic subject, faces the challenge of how to adapt to the modern engineering needs, and strengthening the teaching reform work is crucial for enhancing students’ professional ability as well as promoting their future development. Traditional teaching content and methods have many deficiencies in cultivating students’ comprehensive application ability, and teaching reform is urgently needed. This study discusses the teaching reform strategy of "Engineering Mechanics" from the aspects of updating course content, optimising teaching methods, training teachers and improving students’ abilities. By analysing the necessity of teaching reform, the dilemmas faced and the possible solution paths, it aims to provide theoretical basis and practical reference for the improvement of the course in civil engineering majors.